Animasi Edukatif untuk Meningkatkan Pengetahuan Gizi Anak: Tinjauan Literatur Sistematis - Al - Khaidar; Sarah Rahmatillah; Hermansyah; Husni (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2026)
Childhood nutrition knowledge remains a persistent public health concern, particularly in settings where growth disorders and adolescent obesity coexist. Educational animation has been increasingly adopted as an instructional medium to convey nutrition concepts to children, yet the accumulated evidence has not been synthesized systematically. This study conducted a systematic literature review following the PRISMA 2020 guideline to examine the effectiveness of educational animation in improving children's nutrition knowledge, the animation characteristics associated with successful outcomes, the research trends that emerged between 2020 and 2026, and the gaps that remain for future research. Systematic searches of Scopus, ScienceDirect, PubMed, SpringerLink, Web of Science, IEEE Xplore, Wiley, Taylor & Francis, and ERIC yielded 30 eligible studies after a four-stage screening process. The review found that animated video and game-based interventions consistently produced measurable knowledge gains compared with conventional lecture or printed media, with narrative structure, character relatability, colour use, and multimedia design principles emerging as recurrent contributors to effectiveness. However, most available studies relied on short-term, single-group, quasi-experimental designs concentrated in a limited number of countries, restricting the generalizability of the evidence. This review contributes an integrated, theory-informed synthesis of animation-based nutrition education research and outlines directions for more rigorous, longitudinal, and geographically diverse future studies.